Perbandingan Beberapa Metode Ekstraksi Minyak Atsiri pada Minyak Nilam (Pogostemon cablin) - Ismail Sulaiman (Jurnal Teknologi dan Industri Pertanian Indonesia, 2014)
Extraction method on raw materials patchouli (Pogestemon cablin) can be done by four methods, such as Randall, evaporation, hydro-distillation and DIC. These methods compared to four to get the patchouli alcohol were analyzed by GC MS to produce the optimum amount of essential oils and economically on an industrial scale. Randall and DIC method can be done quickly, while evaporation and hydro-distillation method takes longer, but the hydro-distillation method is more stable and efficient in the process of extraction of essential oils. The time required for the essential oil by Randall method 4 minutes, 3 hours evaporation method, hydro-distillation 7 hours and DIC for 6 minutes. The longer the process of extracting will produce the yield value and need the higher energy.